Flux corrected remapping using piecewise parabolic reconstruction for 2D cell‐centered ALE methods. (28th August 2014) - Velechovsky, J.; Breil, J.; Liska, R.
Summary A novel conservative interpolation (remapping) method, in the Arbitrary Lagrangian–Eulerian context for numerical solution of Euler equations on unstructured polygonal grids, is presented. Combination of a piecewise quadratic reconstruction and a flux corrected remapping approach provides a simple, symmetry‐preserving and bounds‐preserving method. The positivity of density and specific internal energy is guaranteed. The complete description of the method and both cyclic remapping and full hydrodynamic 2D numerical examples are given. Copyright © 2014 John Wiley & Sons, Ltd.